2018
DOI: 10.3389/fneur.2018.00073
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome, Objectively Measured Physical Activity and Exercise Training Interventions: A Systematic Review and Meta-Analysis

Abstract: A systematic review of English and French articles using Pubmed/Medline and Embase included studies assessing objective physical activity levels of obstructive sleep apnea (OSA) patients and exploring the effects of exercise training on OSA severity, body mass index (BMI), sleepiness, and cardiorespiratory fitness [peak oxygen consumption (VO2peak)]. Two independent reviewers analyzed the studies, extracted the data, and assessed the quality of evidence. For objective physical activity levels, eight studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 85 publications
2
79
2
5
Order By: Relevance
“…Prior studies have suggested that high physical activity or exercise levels are associated with reduced symptoms and improved outcomes in patients with existing OSA, irrespective of body weight or BMI (Aiello et al., ; Iftikhar et al., ; Mendelson et al., ; Murillo et al., ; da Silva et al., ). For example, three meta‐analyses of small clinical trials reported that exercise training was independently associated with reduced severity of apnea symptoms in patients with OSA (Aiello et al., ; Iftikhar et al., ; Mendelson et al., ). The underlying mechanisms are not established, but may potentially involve improved strength of pharyngeal dilator muscles, decreased overnight rostral fluid redistribution and stabilization of sympathetic outflow (Iftikhar et al., ; Redolfi et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested that high physical activity or exercise levels are associated with reduced symptoms and improved outcomes in patients with existing OSA, irrespective of body weight or BMI (Aiello et al., ; Iftikhar et al., ; Mendelson et al., ; Murillo et al., ; da Silva et al., ). For example, three meta‐analyses of small clinical trials reported that exercise training was independently associated with reduced severity of apnea symptoms in patients with OSA (Aiello et al., ; Iftikhar et al., ; Mendelson et al., ). The underlying mechanisms are not established, but may potentially involve improved strength of pharyngeal dilator muscles, decreased overnight rostral fluid redistribution and stabilization of sympathetic outflow (Iftikhar et al., ; Redolfi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 1 Characteristics of 18-year-old men who were or were not subsequently diagnosed with sleep apnea, Sweden, 1969Sweden, -2012 To our knowledge, this is the first study to examine CRF in relation to the risk of sleep apnea. Prior studies have suggested that high physical activity or exercise levels are associated with reduced symptoms and improved outcomes in patients with existing OSA, irrespective of body weight or BMI (Aiello et al, 2016;Iftikhar et al, 2014;Mendelson et al, 2018;Murillo et al, 2016;da Silva et al, 2017). For example, three meta-analyses of small clinical trials reported that exercise training was independently associated with reduced severity of apnea symptoms in patients with OSA (Aiello et al, 2016;Iftikhar et al, 2014;Mendelson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small number of studies [10,11,13,31] included in the present meta-analysis reported physical activity levels in OSA and controls. Therefore, we cannot exclude the possibility that patients with OSA had lower levels of physical activity than controls and that this contributed to their lower V′O 2 peak [47].…”
Section: Potential Physiological Mechanismsmentioning
confidence: 99%
“…On the other hand, physical activity was not a significant predictor of mortality after adjusting for CRF [8]. Interestingly, MENDELSON et al [22] have recently showed in a meta-analysis that OSA patients presented low levels of physical activity, with a mean number of steps per day of 5388 (95% CI 3831-6945), far below the recommended threshold of 10 000 steps per day. Moreover, exercise training was associated with significant decrease in apnoea−hypopnoea index, reduction in subjective sleepiness and, notably, increase in V′O 2 peak but no change in BMI [22].…”
mentioning
confidence: 92%